Co-occurrence of microplastics and hydrochar stimulated the methane emission but suppressed nitrous oxide emission from a rice paddy soil. (20th February 2022) - Han, Lanfang; Zhang, Biao; Li, Detian; Chen, Liying; Feng, Yuanyuan; Xue, Lihong; He, Jiehong; Feng, Yanfang
Abstract: Hydrochar (HBC) is an emerging carbon-enriched material produced from renewable resources using hydrothermal carbonization and has performed multiple functions as a soil amendment, including greenhouse gas (GHGs) emission mitigation in croplands. With more and more microplastics (MPs) entering soil, there are concerns about the impacts of the co-occurrence of HBC and MPs on GHGs emissions and the associated microbial communities, which have not been revealed. This study conducted a rice paddy soil column experiment. The co-effects of 0.5 wt% MPs (polyethylene (PE) and polypropylene (PAN)) and 1.0 wt% HBC on nitrous oxide (N2 O) and methane (CH4 ) emissions were investigated relative to treatment of HBC alone and control check (CK). Also, the microbial mechanism regulating N2 O and CH4 emissions has been clarified. Results showed that compared with CK, the addition of HBC alone reduced CH4 cumulative emission by 27.7% although the change was insignificant, but increased N2 O cumulative emission by 66.3%. Overall, HBC alone showed limited impacts on global warming potential (GWP) and greenhouse gas intensity (GHGI). This effect was distinctly altered by PE and PAN addition. The co-occurrence of HBC and PE caused obviously higher methanogens gene ( mcrA ) in soil but lower rice grain yield, leading to the increase of CH4 emissions by 83.5% and GHGIN2O + CH4 by 36.0% compared to HBC alone. While, no apparent difference in CH4 emission occurred between HBC + PAN and HBC. By contrast, HBC + PAN obviously increased N2 O reductase gene ( nos Z ) abundance and decreased the ratio of denitrification gene nir S and nir K to nos Z . Thus, HBC + PAN showed 3- and 4-fold lower N2 O emissions than CK and HBC, respectively. Among all the treatments, HBC + PAN exhibited the strongest GWPN2O + CH4 and GHGIN2O + CH4 mitigation effect. This study firstly demonstrates that the potential of HBC in mitigating GHGs emission in the rice field would greatly and differently vary with the co-occurrence of different types of MPs. Graphical abstract: Image 1 Highlights: Microplastics (PE or PAN) and hydrochar (HBC) co-existed in a rice paddy soil. HBC + PE treatment emitted more CH4 and had higher greenhouse gas intensity than HBC. The methanogen gene was enriched by HBC and PE co-added. HBC + PAN induced more N2 O reductase gene and emitted less N2 O than HBC. HBC + PAN mitigated global warming potential and greenhouse gas intensity.